In search of deeper learning : the quest to remake the American high school - Mehta, Jal; Fine, Sarah M., 1983- (Harvard University Press, 2019)
"An award-winning professor and an accomplished educator, Jal Mehta and Sarah Fine take us beyond the hype of reform and inside some of America's most innovative classrooms to show what is working--and what isn't. In a world where test scores have been king, this boldly humanistic book offers a rich account of what education can be at its best."--